Close association of arterial plaques with left ventricular hypertrophy and ejection fraction in hemodialysis patients - Mowlaie Morteza; Nasri Hamid (Society of Diabetic Nephropathy Prevention, 2014)
Introduction: In renal failure patients, cardiovascular complications are a major clinical problem. Objectives: This study aimed to test, the possible association of left ventricular hypertrophy and ejection fraction with plaques of carotid and femoral artery hemodialysis. Patients and Methods: Sixty-one patients, who were on regular hemodialysis were selected. For all patients echocardiography and B-mode Ultrsonographic assessment of carotid-femoral arteries for plaque occurrence were conducted. Results: In this study there was a positive correlation between left ventricular hypertrophy with the duration of hemodialysis treatment (p<0.05). Significant positive association between left ventricular hypertrophy and plaque score and also a significant positive association between left ventricular hypertrophy with presence of chest pain was found (p<0.05). Association of diabetes mellitus with the presence of chest pain was positive. Positive correlation between hypertension with plaque score was demonstrated too (p<0.05). Also an inverse association of plaque score with left ventricular ejection fraction was detected too (p<0.05). Furthermore, the correlation of plaque score with the presence of diabetes mellitus was positive. Conclusion: The present investigations, documents parallel cardiac and vascular adaptation in hemodialysis patients and shows the potential contribution of structural and functional large artery alteration to the pathogenesis of left ventricular hypertrophy which needs more attention in patients on hemodialysis.